2019
DOI: 10.1007/s11948-019-00167-3
|View full text |Cite
|
Sign up to set email alerts
|

Practices of Responsible Research and Innovation: A Review

Abstract: This paper presents results of a systematic literature review of RRI practices which aimed to gather insights to further both the theoretical and practical development of RRI. Analysing practices of RRI and mapping out main approaches as well as the values, dimensions or characteristics pursued with those practices, can add to understanding of the more conceptual discussions of RRI and enhance the academic debate. The results, based on a corpus of 52 articles, show that practices already reflect the rich varie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 60 publications
3
37
0
1
Order By: Relevance
“…Our analyses suggest RI had a low profile within these research communities prior to 2013. It is important to note that there may well be practices in universities that potentially align with anticipatory, reflexive and deliberative approaches advocated by RI, but which may not be specifically labelled as such (Glerup et al, 2017;Schuijff and Dijkstra, 2020). In their recent review, Schuijff and Dijkstra (2020) note that where such approaches are observed, these tend to be aligned with just one of the RI dimensions described by Stilgoe et al (2013) rather than all four in an integrated manner.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our analyses suggest RI had a low profile within these research communities prior to 2013. It is important to note that there may well be practices in universities that potentially align with anticipatory, reflexive and deliberative approaches advocated by RI, but which may not be specifically labelled as such (Glerup et al, 2017;Schuijff and Dijkstra, 2020). In their recent review, Schuijff and Dijkstra (2020) note that where such approaches are observed, these tend to be aligned with just one of the RI dimensions described by Stilgoe et al (2013) rather than all four in an integrated manner.…”
Section: Discussionmentioning
confidence: 99%
“…But while there have been informative studies of micro practices of RI (e.g. Glerup et al (2017), see also Schuijff and Dijkstra (2020) for a recent review) there has been surprisingly little engagement between scholars of RI and that considerable body of scholarship relating to institutionalisation and the dynamics of organisational change (Genus and Iskandarova, 2018;Randles, 2017). Furthering this exchange is important in terms of providing a theoretically-informed analysis of the dynamics and extent of RI translation within organisations to date (Doezsma et al, 2019;Wedlin and Sahlin, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…RRI emphasises how the acceptability, sustainability, and desirability of an innovation can be enhanced through two-way interaction between stakeholders (De Saille, 2015; Von Schomberg, 2014). Although, scholars have recognized the importance of RRI, it is still a concept in development and much remains unclear about how to operationalise it and how it can stimulate the development of socially robust innovations (Leeuwis & Aarts, 2016;Schuijff & Dijkstra, 2020).…”
Section: The First Objective Of This Dissertation Is To Create An Ovementioning
confidence: 99%
“…Dit laatste punt wordt ook wel het creëren van 'maatschappelijk robuuste' innovaties genoemd. Er is echter nog veel onbekend over hoe stakeholders deze processen in de praktijk kunnen brengen en hoe de interacties daadwerkelijk bijdragen aan legitimiteit en maatschappelijk robuuste innovaties (e.g., Binz et al, 2016;Leeuwis & Aarts, 2011;Schuijff & Dijkstra, 2020).…”
Section: (Summary In Dutch)unclassified
See 1 more Smart Citation